2022
DOI: 10.3389/fonc.2022.927249
|View full text |Cite
|
Sign up to set email alerts
|

C12orf59 Promotes Esophageal Squamous Cell Carcinoma Progression via YAP-Mediated Epithelial-Mesenchymal Transition

Abstract: C12orf59 is a novel gene widely expressed in diverse normal human tissues. Aberrant expression of C12orf59, which is involved in tumor progression, has been reported in a few types of cancer. However, its expression and biological function in esophageal squamous cell carcinoma (ESCC) remain largely unclear. Here, we found that the mRNA and protein levels of C12orf59 were prominently higher in both tumor tissues and most ESCC cell lines. Functionally, C12orf59 overexpression promoted ESCC cell proliferation, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Downstream targets of YAP (Yes-associated protein 1) are determined by its interactions with multiple transcriptional and epigenetic regulators whose expression and activity are dynamically modulated by oncogenic signaling. YAP acts as a transcription cofactor regulating the expression of genes involved in cell proliferation, EMT, and cell migration, all of which contribute to the pro-tumorigenic phenotype [ 20 , 71 , 72 ]. At the same time, it was shown that in different oral SSC cell lines, YAP can be overexpressed or, on the contrary, reduced due to phosphorylation and translocation from the cell nucleus to the cytoplasm [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Downstream targets of YAP (Yes-associated protein 1) are determined by its interactions with multiple transcriptional and epigenetic regulators whose expression and activity are dynamically modulated by oncogenic signaling. YAP acts as a transcription cofactor regulating the expression of genes involved in cell proliferation, EMT, and cell migration, all of which contribute to the pro-tumorigenic phenotype [ 20 , 71 , 72 ]. At the same time, it was shown that in different oral SSC cell lines, YAP can be overexpressed or, on the contrary, reduced due to phosphorylation and translocation from the cell nucleus to the cytoplasm [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“… 10 YAP activation driven by C12orf59, a novel cancer-related factor prominently higher in both tumor tissues and most ESCC cell lines, contributes to the EMT of ESCC, and thereby, combined treatment of C12orf59, and YAP inhibitors could be developed as a therapeutic strategy for metastatic ESCC. 11 Furthermore, a recent study revealed that neuron-specific gene family member 1 may amplify the ERK signaling pathway to promote ESCC cell EMT. 12 Hence, uncovering the molecules driving the EMT process can help identify therapeutic strategies and prolong the survival of patients with metastatic ESCC.…”
Section: Introductionmentioning
confidence: 99%